2008
DOI: 10.1038/bjp.2008.294
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of salvinorin A, from Salvia divinorum, on ileitis‐induced hypermotility: cross‐talk between κ‐opioid and cannabinoid CB1 receptors

Abstract: Background and purpose: Salvinorin A, the active component of the hallucinogenic herb Salvia divinorum, inhibits intestinal motility through activation of k-opioid receptors (KORs). However, this compound may have target(s) other than the KORs in the inflamed gut. Because intestinal inflammation upregulates cannabinoid receptors and endogenous cannabinoids, in the present study we investigated the possible involvement of the endogenous cannabinoid system in salvinorin A-induced delay in motility in the inflame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 59 publications
(93 reference statements)
9
76
0
Order By: Relevance
“…These observations are in accord with earlier studies in animal models, where rewarding effects were observed after administration of low doses of salvinorin A to zebrafish and rats (Braida et al 2007(Braida et al , 2008. The rewarding effects of salvinorin A were also reported by other authors, implicating the involvement or "cross-talk" of the endocannabinoid system in the mechanism of this action (Capasso et al 2008;Walentiny et al 2010). It has been also shown that salvinorin A may decrease responses to cocaine and in this way attenuate cocaine-induced drug-seeking behavior (Chartoff et al 2008;Morani et al 2009Morani et al , 2012.…”
Section: Biological Activitysupporting
confidence: 91%
“…These observations are in accord with earlier studies in animal models, where rewarding effects were observed after administration of low doses of salvinorin A to zebrafish and rats (Braida et al 2007(Braida et al , 2008. The rewarding effects of salvinorin A were also reported by other authors, implicating the involvement or "cross-talk" of the endocannabinoid system in the mechanism of this action (Capasso et al 2008;Walentiny et al 2010). It has been also shown that salvinorin A may decrease responses to cocaine and in this way attenuate cocaine-induced drug-seeking behavior (Chartoff et al 2008;Morani et al 2009Morani et al , 2012.…”
Section: Biological Activitysupporting
confidence: 91%
“…Salvinorin A does not have affinity at CB1 receptors (Roth et al, 2002;Capasso et al, 2008); therefore, this observed effect could be potentially because of a downstream interaction between -opioid and CB1 systems (Mason et al, 1999). However, in contrast to the full blockade observed with nalmefene herein, the CB1 antagonist rimonabant (1 mg/kg i.v.)…”
Section: Discussionmentioning
confidence: 68%
“…Originally, SA was identified as a potent KOR agonist, but recently it has also been shown to possess, unusual for plantderived opioids, the ability to activate CB receptors in in vitro and in vivo assays (Roth et al, 2002;Capasso et al, 2008;Fichna et al, 2009aFichna et al, , 2012Aviello et al, 2011). Here, we observed that the inhibitory effect of PR-38 on twitch contractions in mouse colon in vitro and on the GI motility in vivo was blocked by MOR and KOR antagonists.…”
Section: Discussionmentioning
confidence: 67%
“…Our earlier experimental data suggest that the antimotility action of SA is stronger in pathophysiological conditions than in healthy mice (Capasso et al, 2006(Capasso et al, , 2008, and thus in this study, we used models of diarrhea and hypermotility to evaluate the antidiarrheal properties of PR-38. The administration of PR-38 significantly prolonged the time that elapsed from administration of croton oil to emergence of liquid pellets and significantly altered defecation pattern in stressed mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation